Agenda G20 Dalam Pembangunan Infrastruktur Berkelanjutan (Studi Kasus: Green Bonds dan Green Sukuk di Indonesia) - Dhea Puspita Wardani; Stivani Ismawira Sinambela (JOSH: Journal of Sharia, 2025)
This study examines how the G20 agenda has influenced the development of green bonds and green sukuk as mechanisms for financing sustainable infrastructure in Indonesia during 2018–2024. Employing the Green Politics Theory framework and qualitative descriptive approach with content analysis, the research demonstrates that Indonesia pioneered globally by issuing the world's first sovereign green sukuk worth USD 1.25 billion in 2018, expanding to a cumulative USD 16.93 billion by 2024. These instruments support the achievement of SDG 7 and 13 through projects in sustainable transportation, waste management, and mangrove rehabilitation. The integration of G20 principles into domestic policy—via Climate Budget Tagging, POJK No. 60/2017, and the Sustainable Finance Roadmap—has successfully reduced APBN reliance by 25% and narrowed the budget deficit from 6.14% of GDP (2020) to 2.29% of GDP (2024). Significant challenges persist, including greenwashing risk, limited secondary market liquidity, low institutional capacity, and substantial financing gaps (actual realization represents only 6.8% of needs through 2030). The study concludes that green bonds and green sukuk function as effective catalytic instruments; however, strengthened regulations, institutional capacity building, and cross-sectoral policy integration are essential to accelerate the transition toward sustainable infrastructure.